Intellectuals in politics : from the dreyfus affairto salman rushdie. (Routledge, 1997)
This wide-ranging investigation explores the influence of thinkers from diverse intellectual backgrounds on the development of twentieth century culture, and in so doing tells us much about the modern world in which we live.